Type IVB Secretion Systems of Legionella and Other Gram-Negative Bacteria - Nagai, Hiroki; Kubori, Tomoko (Frontiers in Microbiology, 2011)
Type IV secretion systems (T4SSs) play a central role in the pathogenicity of many important pathogens, including Agrobacterium tumefaciens, Helicobacter pylori and Legionella pneumophila. The T4SSs are related to bacterial conjugation systems, and are classified into two subgroups, type IVA (T4ASS) and type IVB (T4BSS). The T4BSS, which is closely related to conjugation systems of IncI plasmids, was originally found in human pathogen L. pneumophila; pathogenesis by L. pneumophila infection requires functional Dot/Icm T4BSS. A zoonotic pathogen, Coxiella burnetii, and an arthropod pathogen, Rickettsiella grylli—both of which carry T4BSSs highly similar to the Legionella Dot/Icm system—are evolutionarily closely related and comprise a monophyletic group. A growing body of bacterial genomic information now suggests that T4BSSs are not limited to Legionella and related bacteria and IncI plasmids. Here, we review the current knowledge on T4BSS apparatus and component proteins, gained mainly from studies on L. pneumophila Dot/Icm T4BSS. Recent structural studies, along with previous findings, suggest that the Dot/Icm T4BSS contains components with primary or higher-order structures similar to those in other types of secretion systems—types II, III, IVA and VI, thus highlighting the mosaic nature of T4BSS architecture.